2001
DOI: 10.1073/pnas.181177898
|View full text |Cite
|
Sign up to set email alerts
|

Mobilized bone marrow cells repair the infarcted heart, improving function and survival

Abstract: Attempts to repair myocardial infarcts by transplanting cardiomyocytes or skeletal myoblasts have failed to reconstitute healthy myocardium and coronary vessels integrated structurally and functionally with the remaining viable portion of the ventricular wall. The recently discovered growth and transdifferentiation potential of primitive bone marrow cells (BMC) prompted us, in an earlier study, to inject in the border zone of acute infarcts Lin ؊ c-kit POS BMC from syngeneic animals. These BMC differentiated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
1,318
8
35

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,900 publications
(1,389 citation statements)
references
References 41 publications
28
1,318
8
35
Order By: Relevance
“…Consequently, G-CSF is administered to patients suffering from neutropenia, most commonly as a result of chemotherapy after cancer. After administration in mice, G-CSF has been shown to increase the number of circulating bone marrow stem cells (BMC) released into the circulation (Orlic et al, 2001). After myocardial infarct, these BMC migrate to the area of damage and contribute to a significant amount of tissue regeneration (Orlic et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, G-CSF is administered to patients suffering from neutropenia, most commonly as a result of chemotherapy after cancer. After administration in mice, G-CSF has been shown to increase the number of circulating bone marrow stem cells (BMC) released into the circulation (Orlic et al, 2001). After myocardial infarct, these BMC migrate to the area of damage and contribute to a significant amount of tissue regeneration (Orlic et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…After administration in mice, G-CSF has been shown to increase the number of circulating bone marrow stem cells (BMC) released into the circulation (Orlic et al, 2001). After myocardial infarct, these BMC migrate to the area of damage and contribute to a significant amount of tissue regeneration (Orlic et al, 2001). After cerebral ischemia, it has been observed that either transplanted (Chen et al, 2001) or intravenously administered BMC (Chopp and Li, 2003) infiltrate into the lesion area.…”
Section: Discussionmentioning
confidence: 99%
“…This provides the required stimulus for mobilization of stem cells from BM niches to the damaged site as a part of a natural repair process [9]. The other key players involved in tissue ischemia-induced mobilization of BM progenitors to the circulation include vascular endothelial growth factor, placenta growth factor, stem cell factor, and granulocyte colony stimulating factor [10][11][12][13]. The effect of intrinsic SDF-1α up-regulated expression is, however, transient and insufficient for cardiac repair [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, bone marrow cells, including isolated populations of hematopoietic stem cells have been reported to differentiate into muscle, neurons, liver, vascular, lung, intestine and kidney tissue (Yoder, 2004). In addition, it has been shown that stem cells obtained from adult bone marrow not only were able to differentiate into cardiomyocytes but also contributed to restore cardiac function when either injected directly into the injured adult heart (Tomita et al, 1999) or exposed to myocardium via circulation (Orlic et al, 2001). Two distinct types of stem cells are currently known to reside within adult bone marrow: hematopoietic and mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%